Emparejamiento entre desempleados y vacantes para Cali entre 1994 y 2005: Un análisis con datos de panel. (2007)
This paper discuss the matching process between unemployment and vacancies in the labor market of Santiago de Cali city through the matching function with data panel between 1994 to 2005 using the SPE - SENA data. The results show increasing returns in the matching function with respect to the performance area in the National Classification of Occupations, (CNO in Spanish).